STRATEGIES AND MODELS OF HIMPAUDI MENTORING IN KRUI, WEST PESISIR, FOR DEVELOPING EARLY CHILDHOOD TEACHER PROFESSIONALISM - Suliani Suliani; Joko Pamungkas (PT. Jurnal Center Indonesia Publisher, 2026)
This study describes the strategies and mentoring model implemented by HIMPAUDI in Krui, West Pesisir Regency, to improve the professionalism of early childhood education teachers. This research employed a descriptive qualitative approach, with primary data collected through a structured interview with a HIMPAUDI board member in West Pesisir Regency. The findings show that HIMPAUDI mentoring is carried out through tiered training, curriculum and learning workshops, teacher working groups, seminars, mentoring, supervision, sharing of good practices, and socialization of professional ethics. The mentoring model is participatory, collaborative, continuous, needs-based, reflective, and ethical-professional. These activities strengthen teachers pedagogical, professional, social, and personal competencies, particularly in understanding child development, designing creative learning, developing learning media, adapting the curriculum, and maintaining professional responsibility. However, implementation is constrained by limited time, training costs, unequal access to information, varied teacher motivation, digital competence, and coastal geographical conditions. The study recommends strengthening local professional development through professional learning communities, mentoring cycles, digital support, and institutional collaboration among HIMPAUDI, local government, higher education institutions, and early childhood education providers.